Non-fragile sliding mode control for one-sided Lipschitz chaotic systems. (May 2022) - Huang, Jun; Yang, Genke; Fang, Zhijun; Duan, Qianqian; Ju, Changjiang; Gao, Xiumin
Abstract: This paper deals with the sliding mode stabilization for chaotic systems. In the system under consideration, the nonlinear function is one-sided Lipschitz with quadratic inner-boundedness. Specifically, a non-fragile sliding mode surface is constructed, and the sufficient condition for the convergence is derived. Then, a new feedback law is proposed to enable the state trajectories of the closed-loop system to reach the sliding mode surface in finite time. Finally, an example in the background of the unified chaos system is simulated to show the validation of the designed controller.